The Switch From Infinitive to Subjunctive Clauses in Romanian - Motapanyane, Virginia (Papers from the Annual Meetings of the Atlantic Provinces Linguistic Association (PAMAPLA) / ACTES DES COLLOQUES ANNUELS DE L’ASSOCIATION DE LINGUISTIQUE DES PROVINCES ATLANTIQUES (ACAALPA)., 1991)
This paper focuses on the syntactic properties of subjunctive complement clauses in Romanian. The peculiarity of these structures consists in two empirical facts : (i) the subjunctive cannot alternate with the infinitive in complement position - a common option in other Romance languages; (ii) word order is restricted to VSO in COMP-less subjunctive complements, although the SVO/VSO option is free in all other contexts. I propose a generative approach to these constructions within the framework of Government and Binding Theory (cf. Chomsky (1981)). The purpose of my analysis is to account for the phenomena in (i) and (ii) through specific constraints applying in the underlying structure of a subjunctive clause. The outcome of this analysis will show that Romanian follows the syntactic pattern of Romance languages in these structural contexts. This conclusion weakens the usual relation between Romanian and Greek, a neighbouring language where a similar switch from infinitive to subjunctive complements took place.